The possibilities of Surrealist Photography to Architectural Design and Proposition - Loizos, Yorgos (Architecture Image Studies, 2020)
This paper aims to look at the spatial opportunities that Surrealist photography can bring to architectural design, and in particular learning from the work of Man Ray and László Moholy-Nagy and their photograms, models and light devices. It explores what makes architecture and photography similar, by studying aspects of light sensitive surfaces and spaces, juxtapositions of different scales and the relationship between the photograph, the photographed user and building. It provides a practical study, the design and narrative of an experimental house entitled ‘Analogical House’. The house, a rig structure that is simultaneously made as a device to create drawings and a set of room fragments and kinetic components, allows to creatively challenge the conventional architectural drawings. These drawings communicate light conditions, distances of objects, as well as they record unexpected moments, happy accidents and glitches, which become opportunities to learn from and to adapt the design of the house.